Parade of militia down Steadman Ave. for the July 4th celebration, Nome, Alaska, 1901. - Hegg, Eric A., 1867-1948 (1901)
Caption on image: "Coming down Steadman Ave., Nome. July 4 1901" Original image in Hegg Album 38, page 55.